Functional outcomes in patients with co-occurring traumatic brain injury and spinal cord injury from an inpatient rehabilitation facility's perspective. (2nd November 2018) - Garlanger, Kristin L.; Beck, Lisa A.; Cheville, Andrea L.
Abstract : Objective: To examine the occurrence and severity of co-occurring traumatic brain injury (TBI) in persons with traumatic spinal cord injury (SCI), i.e. dual diagnosis (DD), and to describe differences in functional outcomes between persons with DD and SCI only from an inpatient rehabilitation facility (IRF) perspective. Design: Retrospective clinical chart review. Setting: Acute Midwest SCI inpatient rehabilitation facility. Participants: 256 persons age 18-80 years with acute traumatic SCI (AIS A-E, C1-S3 level of injury) from 2002-2012. Interventions: Neuroimaging and electronic medical records were reviewed to identify those with co-occurring TBI. Outcomes were then compared between the SCI only and DD groups. Outcome Measures: Length of stay (LOS), discharge location and functional independence measures (FIM) Results: Forty-one percent of persons with traumatic SCI experienced co-occurring TBI. Rehabilitation LOS for the DD groups did not differ significantly from the SCI only group. Those with Moderate-Severe DD had significantly lower Total admission FIM (P < 0.001), Cognitive admission and discharge FIM (both P < 0.001) and Motor FIM efficiency scores (P = 0.03) compared to those with SCI only and were significantly less likely to discharge home (P = 0.05). Conclusions: Persons admitted to IRFs with Moderate-Severe DD compared to those with SCI only are less efficient in obtaining motor skills and may require ongoing rehabilitation to safely return home. It is therefore imperative to initiate early discharge planning and educate rehabilitation team members and families on the additional time and resources necessary to achieve more successful outcomes in those with Moderate-Severe DD.